CBML: CLASSIFICATION – THAI RED DRAGON FRUIT - Yusamran, Naruwan; Hiransakolwong, Nualsawat (My University, 2022)
A dragon fruit is nutritious having low sugar levels suitable for diabetics. Its shape is spherical with petals surrounding the bark. In Thailand, 7 species of dragon fruit are grown. Its appearance can be divided into red bark (6 species) or yellow bark (1 species). People can separate between yellow and red bark. Since the red-skinned dragon fruit may have its fruit pulp in one of three possible colors: white, red or pink, it is difficult to guess from the outside what color of the fruit pulp will be. The big problem is that people cannot classify its species of red bark. Some people may be allergic or dislike dragon fruit in some species. Therefore, this research is trying to find the best way to automatically classify the species of Thai red dragon fruit from its image. The CBML stands for content base and Machine Learning. This method uses content base to extract key features (34 attributes), and uses Machine Learning for giving optimization results with the Support Vector Machine (SVM), setting kernel for polynomial in 8 degree. The results showed that the CBML method was able to identify any species of dragon fruits in the red bark group with an accuracy of 98.47%.
Keywords: Classification; Content base; Dragon fruit; Machine Learning